Considerations from the 2017 IMFAR Preconference on Measuring Meaningful Outcomes from School‐Age to Adulthood. Issue 11 (30th October 2018) - Bal, Vanessa H.; Hendren, Robert L.; Charman, Tony; Abbeduto, Leonard; Kasari, Connie; Klinger, Laura Grofer; Ence, Whitney; Glavin, Tara; Lyons, Gregory; Rosenberg, Erin
Abstract : The autism spectrum disorder (ASD) research community is increasingly considering the importance of measuring outcomes that are meaningful to individuals with ASD and their families. The 2017 IMFAR preconference aimed to gain the perspectives of how to define and measure "meaningful outcomes" from 280 participants, including people with ASD and their families, service providers, and researchers. Six themes were identified: (a) the definition of "outcome" varies by context and perspective; (b) the need to broaden the scope of what researchers measure; (c) the need for new assessment tools; (d) the need to expand data analytic methods; (e) where to focus (with emphasis on considering different developmental stages and aspects of diversity); and (f) a need for community partnerships to bridge research and daily practice. The challenge that the research community now faces is how to move the evidence base for clinical practice forward while keeping alive the divergence of views and considerations that are relevant for thinking about complex outcomes for the highly heterogeneous group of individuals with ASD. This commentary provides recommendations, with an emphasis on lifespan viewpoints that encompass individual strengths and preferences. Autism Research 2018, 11: 1446–1454 . © 2018 International Society for Autism Research, Wiley Periodicals, Inc. Lay Summary: The 2017 IMFAR preconference aimed to gain the perspectives of how to define and measure "meaningful outcomes" from a variety of stakeholders. This commentary outlines the six themes identified from keynote and panel presentations and audience‐participated discussions. Recommendations are made to emphasize perspectives that look across the lifespan and encompass individual strengths and preferences.